2017
DOI: 10.1002/cssc.201700128
|View full text |Cite
|
Sign up to set email alerts
|

Direct Synthesis of Dimethyl Carbonate from Carbon Dioxide and Methanol at Room Temperature Using Imidazolium Hydrogen Carbonate Ionic Liquid as a Recyclable Catalyst and Dehydrant

Abstract: The direct synthesis of dimethyl carbonate (DMC) from CO and CH OH was achieved at room temperature with 74 % CH OH conversion in the presence of an imidazolium hydrogen carbonate ionic liquid ([C C Im][HCO ]). Experimental and theoretical results reveal that [C C Im][HCO ] can transform quickly into a CO adduct, which serves as an effective catalyst and dehydrant. Its dehydration ability is reversible. The energy barrier of the rate-determining step for the DMC synthesis is only 21.7 kcal mol . The ionic liqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(49 citation statements)
references
References 132 publications
1
48
0
Order By: Relevance
“…Among them hydrogen carbonate and hydroxide are particularly important. As regards 1,3-dialkylimidazolium hydrogen carbonates, it is reported that these ionic liquids are in equilibrium with the corresponding NHC-CO 2 adducts (vide infra), demonstrating the possibility to afford NHCs (see for example: Fèvre et al, 2012; Zhao et al, 2017) by releasing of carbon dioxide due to high temperature effect or, at room temperature, using a solvent favoring the carbene generation (as THF or toluene).…”
Section: Experimental Studiesmentioning
confidence: 99%
“…Among them hydrogen carbonate and hydroxide are particularly important. As regards 1,3-dialkylimidazolium hydrogen carbonates, it is reported that these ionic liquids are in equilibrium with the corresponding NHC-CO 2 adducts (vide infra), demonstrating the possibility to afford NHCs (see for example: Fèvre et al, 2012; Zhao et al, 2017) by releasing of carbon dioxide due to high temperature effect or, at room temperature, using a solvent favoring the carbene generation (as THF or toluene).…”
Section: Experimental Studiesmentioning
confidence: 99%
“…However, the equilibrium of the direct esterification of carbon dioxide and methanol is unfavorable , wherefore the reaction only proceeds when the by‐product water is effectively removed from the reaction mixture. This was attempted, e.g., by the use of dehydrating agents like 2‐cyanopyridine , molecular sieves , ionic liquids , or for the similar diethyl carbonate by the separation of water through a membrane . The stoichiometrically used dehydrating agent 2‐cyanopyridine in a continuous flow setup at 120 °C (∼10 min residence time) leads to excellent conversion and selectivity, but the subsequent dehydration of the produced 2‐picolinamide for recycling is unfavorable (17 days at 165 °C) .…”
Section: Strategies Towards (Higher) Alcohols With Homogeneous Catalymentioning
confidence: 99%
“…The further mentioned dehydrating agents as well as the membrane technics could provide a better recyclability, but the esterification reaction proceeds way slower (e.g. 75 % conversion after 24 hours) . In context of the homologation reaction, the efficiency of the recyclable dehydrating agent may be improved because dimethyl carbonate is used as an intermediate itself and can also be removed from the reaction mixture (Scheme ).…”
Section: Strategies Towards (Higher) Alcohols With Homogeneous Catalymentioning
confidence: 99%
“…The produced basic carbonate/bicarbonate can then deprotonate the imidazolium cation forming the NHC-carbene, which regenerates the zwitterion BMIm.CO 2 by interaction with CO 2 (Scheme 2). [24] Notably, no other species were observedb yt he ESI-MS and NMR analysis of the aqueous solution after the reaction. [24] The 1 Ha nd 13 CNMR spectra of the aqueous phase of BMIm.CO 2 IL confirmedt he generationo fC O 3 2À upon performing the reaction under argon ( Figures S2 and S3).…”
Section: Introductionmentioning
confidence: 98%
“…[21] Therefore, the possible reaction pathways involved in the CO 2 photoreduction occur through the formation of [CO 2 ]C À that reacts with CO 2 to generate the ]C À that, by addition of another [CO 2 ]C À ,produces CO and carbonate as observed in the electrochemicalreductions(Scheme2). [24] The 1 Ha nd 13 CNMR spectra of the aqueous phase of BMIm.CO 2 IL confirmedt he generationo fC O 3 2À upon performing the reaction under argon ( Figures S2 and S3). The produced basic carbonate/bicarbonate can then deprotonate the imidazolium cation forming the NHC-carbene, which regenerates the zwitterion BMIm.CO 2 by interaction with CO 2 (Scheme 2).…”
Section: Introductionmentioning
confidence: 99%